Distribution of Tree and Shrub Vegetation in some Foothill Forests of Garhwal Himalayas - Kumar, Aravind; Singh, Bhim; Prabha, Shashi (Indian Forester, 2008)
As many as 45 species of trees and 31 species of shrubs were found in the foothill forests of Garhwal Himalayas but without exhibiting domination by any particular species. The trees of Cassia fistula, Haldina cordifolia, Holoptelea integrifolia and Mallotus philippensis were recorded at all the slopes and sites throughout the forests whereas species like Alangium salvifolium, Bauhinia purpurea, B. racemosa, Bombax ceiba, Crataeva nurvala, Dalbergia lanceolaria, Dalbergia sissoo, Ficus palmata, Grewia oppositifolia, Mitragyna parviflora, Moringa oleifera, Ougeinia oujeinensis, Sapium insigne, Stereospermum suaveolens and Trema politoria were sporadic in distribution and were recorded only at a few places in the forests under study. The remaining species were distributed unevenly. Numerically, 35 tree species were recorded in lower forests growing near the riverside, 32 species in the forests of lower/ middle slopes and 33 species at the upper ridges of the hills. The trees of Terminalia bellirica exhibited the highest average circumference (249.12cm), followed by Albizia julibrissin (195.2cm), Adina cordifolia (188.77cm), Alstonia scholaris (162.79cm), Schleichera oleosa (146.39cm), Bombax ceiba (142.12 cm) and Terminalia alata (138.03cm). Minimum average circumference was recorded for Holarrhena antidysenterica (31.78 cm) among all the tree species growing in the forests under study. Among shrubs species recorded in the area, Adhatoda vasica and Murraya koenigii were quite abundant in most of the forests. Maximum similarity among various forests stands, both for trees and shrubs, were between the Similarity Class 60-80%. The absence of Similarity Class below 40% indicated that the forests were not much disturbed.